Pencegahan Kerusakan Fisiologis Belimbing (Avverhoa carambola) dalam Rantai Pasok dengan Optimisasi Model Kombinasi Perlakuan Air Panas dan CaCl2 Menggunakan Response Surface Method - . Sutrisno; Emmy Darmawati; Rokhani Hasbullah; Harli Prawaningrum (Jurnal Ilmu Pertanian Indonesia, 2013)
Starfruits is one of exotic tropical fruits that have increasing its popularity both for domestic and global market due to its unique shape and taste, as well as their nutrition values. However, this fruit is considered perishable product with short self-life, thus the proper post harvest treatment should be done to prevent their quality after harvest. In general, the objective of this research was to determine optimum treatment of hot water treatment (HWT) and immersion period in CaCl2 solution using response surface method (RSM) for post harvest handling of starfruits in order to maintain its quality during storage. Among quality parameters tested, weight loss and hardness were found as the most responsive to the combination treatment. Parameter of weight loss rate showed a maximization response with stationary point of HWT’s temperature of 42 °C, expose period for 42 minutes, and immersion period in CaCl2 solution for 38 minutes with respond point of weight loss was 3.74%. Meanwhile, the hardness parameter achievement was the minimum with stationary point of HWT’s temperature of 48 °C, expose period for 35 minutes, and immersion period in CaCl2 solution fpr 35 minutes resulted respond point of hardness of 0.63 Newton. Interest level from the panelist were color, taste, texture and aroma, respectively, whereas the treatment combination that accepted by panelist were (45 °C, 65', 40'), (45 °C, 40', 15'), and (45 °C, 40', 40’).